Autoimmune Connective Tissue Diseases and the Risk of Rotator Cuff Repair Surgery: A Population-Based Retrospective Cohort Study. Issue 2 (25th February 2019) - Huang, Shih-Wei; Lin, Che-Li; Lin, Li-Fong; Huang, Chi-Chang; Liou, Tsan-Hon; Lin, Hui-Wen
Abstract : Objectives: Autoimmune connective tissue diseases (ACTDs) commonly involve the shoulder joint; however, clinical epidemiological studies investigating their association with tendons are scant. Rotator cuff (RC) tears can cause shoulder disability, and surgical intervention is usually required. The study investigated RC repair surgery risk in ACTD patients. The effect of anti-inflammatory medication on RC repair surgery risk was also investigated. Methods: We conducted a retrospective cohort study with a 7-year longitudinal follow-up period. Patients with systemic lupus erythematosus, systemic sclerosis, sicca syndrome, dermatomyositis and polymyositis diagnoses between 2004 and 2008 were enrolled. The control cohort comprised age- and sex-matched controls. The HR and adjusted HR (aHR) were estimated for the risk of RC surgery between ACTD and control cohorts after adjustment for confounders. Furthermore, the effects of steroid and non-steroidal anti-inflammatory drug (NSAID) use on the HR and aHR of RC surgery risk were analysed. Results: We enrolled 5019 ACTD patients and 25 095 controls in the ACTD and control cohorts, respectively. RC surgery incidence was 49 and 24 per 100 000 person-years in the ACTD and control cohorts, respectively. In the ACTD cohort, the crude HR for RC surgery was 2.08 (95% CI, 1.08 to 4.02, p<0.05), and the aHR was 1.97 (95% CI, 1.01 to 3.82, p<0.05). The ACTD patients who used NSAIDs had an aHR of 3.13 (95% CI, 1.21 to 8.07, p<0.05) compared with the controls, but the ACTD patients who used steroids did not have a significantly higher aHR than the controls. Conclusions: ACTD patients had an increased risk of RC repair surgery. However, no difference was found in RC surgery risk when steroids were used compared with the control cohort. This could indicate that inflammation control may be a strategy for managing subsequent RC lesions.